Expected benefits and drawbacks of Baltic Sea European transport corridors—Implications for complementary governance of TEN-T Core network corridors - Maria Öberg; Kristina L. Nilsson; Charlotta M. Johansson (Cogent Business & Management, 2018)
In this paper, stakeholders' expected benefits and concerns are presented regarding the development of Core Network Corridors (CNCs) within the European transport initiative, the Trans-European Network for Transports. An interview study was conducted with 23 stakeholders from different parts of the society in the Baltic Sea area. The results show that stakeholders have a range of expectations, both positive and negative, for the development of the CNC. Stakeholders' views were sorted into three categories based on the gathered data: matters that are already regulated; unregulated matters that often include vaguely defined responsibilities and require diverse stakeholder engagement for improvement; and matters for which there are concerns about negative outcomes. The results indicate (a) a need for cost-effective complementary governance, here described as additional governance measures to those regulated in the initial framework, (b) that a wider group of stakeholders than is currently involved is needed in the on-going implementation process. Additional regional and local level stakeholders, within and outside of the CNC, and private businesses, would enhance the benefits and/or mitigate negative implications of the developed CNCs, (c) an openness for complementary governance in the on-going CNC implementation process. This openness needs to be considered when developing models for policy packaging.
Keywords: 650